Almacenamiento de hidrógeno en carbones activados por oxidación con aire (2007)
ABSTRACT: In this work, hydrogen adsorption was studied over an activated carbon using oxidative techniques. The influence of the time of oxidation of the carbonaceous material on the H2 storage capacity was evaluated. Hydrogen adsorption experiments were carried out at low temperatures (77 K) using a volumetric method and at high pressures (10, 20 and 30 atm) using a gravimetric method. The results indicated that char oxidation modifies the inner structure of the material which increases the storage capacity of hydrogen.